Modelling the out of plane seismic behaviour of masonry walls by rigid elements. - Casolo, Siro
A computational model for evaluating the dynamical response and the damage of large masonry walls subjected to out of plane seismic actions is presented. During earthquakes, these actions are often the main cause of damage for the front wall and lateral walls of old masonry built churches and monuments. Since the crack patterns often tend to subdivide the plane walls into a number of blocks, the model assumes such walls as a series of quadrilateral plane rigid elements connected to each other in the middle of their adjoining sides. Only the out of plane displacements are considered, and the connections are regarded as spherical elasto-plastic joints which allow rotations whose axis is in the plane of the undeformed wall. The hysteretic characteristics of these joints are defined so as to approximate the brittle behaviour of masonry material and the degradation due to cyclic loadings. The numerical results obtained using a limited number of elements show that the global out of plane response of the masonry walls and the mechanical degradation at each connection are in accord with the observed behaviour of real churches hit by strong earthquakes.
Keywords: Rigid elements; Masonry; Hysteretic behaviour; Plate; Orthotropy; Dynamics